Grape Seed Procyanidin Extract Improves Insulin Production but Enhances Bax Protein Expression in Cafeteria-Treated Male Rats - Lídia Cedó; Anna Castell-Auví; Victor Pallarès; Mayte Blay; Anna Ardévol; Montserrat Pinent (International Journal of Food Science)
In a previous study, the administration of a grape seed procyanidin extract (GSPE) in female Wistar rats improved insulin resistance, reduced insulin production, and modulated apoptosis biomarkers in the pancreas. Considering that pharmacokinetic and pharmacodynamic parameters in females are different from these parameters in males, the aim of the present study was to evaluate the effects of GSPE on male Wistar cafeteria-induced obese rats. The results have confirmed that the cafeteria model is a robust model mimicking a prediabetic state, as these rats display insulin resistance, increased insulin synthesis and secretion, and increased apoptosis in the pancreas. In addition, GSPE treatment (25 mg/kg of GSPE for 21 days) in male rats improves insulin resistance and counteracts the cafeteria-induced effects on insulin synthesis. However, the administration of the extract enhances the cafeteria-induced increase in Bax protein levels, suggesting increased apoptosis. This result contradicts previous results from cafeteria-fed female rats, in which GSPE seemed to counteract the increased apoptosis induced by the cafeteria diet.